PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN SECARA PEMBELAAN TERPAKSA MELAMPAUI BATAS - faris laia (LPPM Universitas Nias Raya, 2026)
Proving a criminal charge of murder committed under circumstances of excessive necessary defense involves determining whether the act of taking another person's life meets the elements of the crime of murder or falls under a justification that negates the unlawfulness of the act. This study employs a normative legal research method, utilizing both conceptual and statutory approaches. The objective of the research is to examine the evidentiary process regarding murder committed through excessive necessary defense. The findings indicate that while the evidentiary process is rigorously conducted by law enforcement given that murder is inherently an unlawful act it is crucial to recognize the role of